Hexafluoroisopropanol (HFIP) as a Multifunctional Agent in Gold-Catalyzed Cycloisomerizations and Sequential Transformations - Tzouras, Nikolaos V.; Zorba, Leandros P.; Kaplanai, Entzy; Tsoureas, Nikolaos; Nelson, David J.; Nolan, Steven P.; Georgios C. Vougioukalakis (ACS Catalysis, 2023)
Despite the unique position of gold catalysis in contemporary organic synthesis, this area of research is notorious for requiring activators and/or additives that enable catalysis by generating cationic forms of gold catalysts. Cycloisomerization reactions occupy a significant portion of the gold-catalyzed reaction space, while they represent a diverse family of reactions that are frequently utilized in synthesis. Herein, hexafluoroisopropanol (HFIP) is shown to be a uniquely simple tool for gold-catalyzed cycloisomerizations, rendering the use of external activators obsolete and leading to highly active catalytic systems with ppm levels of catalyst loading in certain cases. HFIP assumes a dual role as a solvent and an activator, operating via the dynamic activation of the Au-Cl bond through hydrogen bonding, which initiates the catalytic cycle. This special mode of catalysis can enable efficient and scalable cyclization reactions of propargylamides and ynoic acids with simple [AuCl(L)] complexes. A thorough screening of ancillary ligands and counter anions has been performed, establishing this methodology as an alternative to elaborate ligand/catalyst design and to the use of activators. Additionally, this concept is applied in C-C bond-forming cycloisomerization reactions leading to 2H-chromenes and to the design of catalytic systems for sequential or one-pot transformations leading to activated ketoesters, a functionalized N-heterocyclic carbene (NHC) precursor salt, and a compound bearing the bioactive indole core, among others. Importantly, through mechanistic investigations, including a “snapshot” of the species of interest in the solid state, we were able to unambiguously detect the key H-bonding interaction between HFIP and the gold catalyst, shedding light on the intermolecular mode of activation that enables catalysis. In the cases examined herein, HFIP is not only an excellent solvent but also a potent activator and a valuable synthetic handle when incorporated into functional groups of products.
Keywords: cycloisomerizations; gold catalysis; hexafluoroisopropanol; Hydrogen Bonding; Mechanistic studies; N-heterocyclic carbene